How Shopping Lifestyle Moderates the Effect of Product Variety and Store Atmosphere on Impulse Buying - Payanti, Ni Made Ari Dewi; Imbayani, I Gusti Ayu; Prayoga, I Made Surya (Journal of International Conference Proceedings, 2023)
Impulse buying is one of the effective steps that can be taken to improve marketing. Although impulse buying is seen as a negative stigma for shopper, for business actors, impulse buying is an opportunity that must be maximized with the right marketing strategy.The sampling technique was carried out using non probabilty sampling technique with accidental sampling method. The number of samples taken was 95 people who were shopper of Kanini Jewelry products who were or had purchased products from the Bali branch of Kanini Jewelry. The analysis techniques used in this study are multiple linear regresion tests, t tests and moderated regresion analysis (MRA) tests, using the IBM SPSS. The results of this study are product variety and store atmosphere have a positive and significant efect on impulse buying, shopping lifestyle moderates the efect of product variety and store atmosphere on impulse buying. So it is important for companies to pay attention to product variations and store atmosphere and shopping lifestyle of shopper.